SUPPLIER PERFORMANCE EVALUATION WITH AHP AND FUZZY AHP METHOD (CASE STUDY: PT. X) - Yuli Setiawannie (Universitas Potensi Utama, 2016)
Suppliers have an important role in supply chain management. Supplier performance evaluation is complex and unstructured problem and involve multi criteria. The weighting method that used is AHP and fuzzy AHP. Fuzzy AHP method is employed to solve the uncertainty and vagueness from subjective perception and the experiences of human in decision making. Determination of supplier performance weight with fuzzy AHP is more accurate and appropriate company need. Sensitivity analysis indicated that a difference final weight supplier but it didn’t change ranking of priority supplier in AHP and fuzzy AHP method.